Using a brain-like endothelial cell differentiation to characterize the CS79iBRCA-n2 BRCA1 mutated patient derived stem cell line - Natalie G. Alexander; Kylie A. Buchanan; Alexandra E. Meyer; Lauren M. Mitterway; Caroline O. Vanderburgh; Shreyas S. Rao; Shreyas S. Rao; Shreyas S. Rao; Brandon J. Kim; Brandon J. Kim; Brandon J. Kim; Brandon J. Kim; et al. (Frontiers in Cell and Developmental Biology)
BRCA1/2 genes are considered tumor suppressor genes and help repair damaged DNA. Pathogenic germline mutations of BRCA1/2 genes are the most common hereditary cause of breast cancer and ovarian cancer. It has been established that BRCA1 mutations increase the risk of brain metastasis compared to the BRCA1 wildtype, and once metastasis occurs to the brain the disease is considered uncurable. The blood-brain barrier (BBB) is essential for maintaining and regulating homeostasis of the central nervous system and is composed of highly specialized brain endothelial cells. Using a human induced pluripotent stem cell (hiPSC) based model, we characterized an hiPSC line from an invasive cancer patient harboring a BRCA1 mutation. This patient-derived hiPSC line can be utilized to study BBB properties as after differentiation into brain-like endothelial cells (BECs), BECs derived from this line express BBB markers such as tight junction proteins, and functional efflux transporters. Future application of patient-derived stem cell models could provide a platform to discover genetic predispositions to BBB disruption in individuals with BRCA1 mutations, as well as the potential molecular mechanisms contributing to brain metastasis.